The Development of a Seamless Health Service Model for Breast Cancer Patients from Hospital to Community - Petchsuk, Raphatphorn; Cheevakasemsook, Aree; Seanprasarn, Penchun (Journal of The Royal Thai Army Nurses, 2025)
The objectives of this Qualitative research aimed: to analyze situation of a health service model of a cancer hospital, to develop a seamless health service model for breast cancer patients from Hospital to Community, and to evaluate the appropriateness of the developed model. The key informants were purposively selected and divided into two groups: the healthcare team and patients and caregivers. The research instruments included two sets: a question guideline for focus group discussions, and an assessment form for evaluating the appropriateness of the seamless healthcare service model for breast cancer patients from hospital to community. Both instruments were validated for content accuracy by five experts. The research findings revealed as follows. The current situation of the healthcare service model for breast cancer patients in a cancer hospital could be there were policies aligned with the healthcare service development plan and tertiary care processes. Communication and coordination were facilitated by technologies but they lacked consistency and continuity. Health personnel were limited, and staff at sub-district hospitals were also overburdened with a heavy workload. There were procedures for patient care during hospitalization and after discharge, but there was a lack of a seamless care approach. Post-discharge patient follow-up was not comprehensive. The developed seamless healthcare service model consisted of structure and process aspects were developed based on situation exploration and the integration of two key concepts of seamless healthcare services and Donabedian’s quality of care evaluation. Finally, the developed seamless healthcare service model demonstrated an appropriateness rate of 91.90%.